Pengaruh Kualitas Pelayanan terhadap Kepuasan dan Dampaknya pada Loyalitas Nasabah di LPD Desa Adat Panji Kecamatan Sukasada - Krisdianti, Ni G.A Kt. Rada; Sujana, I Nyoman (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
The purpose of this study was to determine the effect of service quality on satisfaction and its impact on customer loyalty in the LPD Desa Adat Panji, Sukasada District. This study used a causality research design. The population of this study were all customers of LPD Desa Adat Panji with a sample of 373 respondents who were searched using purposive sampling. Data collection using a questionnaire was analyzed using path analysis assisted by SPSS 20.0 for Windows. The results showed that service quality can have a direct effect on customer loyalty and can also have an indirect effect, namely service quality on customer loyalty through customer satisfaction (as an intervening variable). The magnitude of the direct effect is 0.044, while the magnitude of the indirect effect is 0.109. Because the coefficient of indirect influence is greater than the direct coefficient, it can be concluded that customer loyalty is more dominantly influenced by indirect relationships through customer satisfaction. in other words, customer satisfaction in supporting customer loyalty in explaining the effect of service quality is relatively high.